2014
DOI: 10.1371/journal.pone.0093953
|View full text |Cite
|
Sign up to set email alerts
|

A Trisubstituted Benzimidazole Cell Division Inhibitor with Efficacy against Mycobacterium tuberculosis

Abstract: Trisubstituted benzimidazoles have demonstrated potency against Gram-positive and Gram-negative bacterial pathogens. Previously, a library of novel trisubstituted benzimidazoles was constructed for high throughput screening, and compounds were identified that exhibited potency against M. tuberculosis H37Rv and clinical isolates, and were not toxic to Vero cells. A new series of 2-cyclohexyl-5-acylamino-6-N, N-dimethylaminobenzimidazoles derivatives has been developed based on SAR studies. Screening identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…94 SB-P3G2 and SB-P8B2 were found to have modest activity against non-replicating M. tuberculosis cells grown under low oxygen conditions, which suggested that this series of compounds might have efficacy against latent TB infections. 95 In the in vivo efficacy study of SB-P3G2 and SB-P17G-A20 using an acute TB infection model in GKO mice showed SB-P3G2 reduced the bacterial load of M. tuberculosis H37Rv by 0.7 ± 0.17 log 10 CFU in the lungs and 0.41 ± 0.36 log 10 CFU in spleen, 95 while SB-P17G-A20 reduced the bacterial load by 1.73 ± 0.24 log 10 CFU and 2.68 ± 0.48 log 10 CFU in lungs and spleen, respectively.…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%
“…94 SB-P3G2 and SB-P8B2 were found to have modest activity against non-replicating M. tuberculosis cells grown under low oxygen conditions, which suggested that this series of compounds might have efficacy against latent TB infections. 95 In the in vivo efficacy study of SB-P3G2 and SB-P17G-A20 using an acute TB infection model in GKO mice showed SB-P3G2 reduced the bacterial load of M. tuberculosis H37Rv by 0.7 ± 0.17 log 10 CFU in the lungs and 0.41 ± 0.36 log 10 CFU in spleen, 95 while SB-P17G-A20 reduced the bacterial load by 1.73 ± 0.24 log 10 CFU and 2.68 ± 0.48 log 10 CFU in lungs and spleen, respectively.…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%
“…To assess the performance of the SMEDDS formulation on the delivery and efficacy of diphenyl ether lead candidates, and co-treatment, SB-PT070 and SB-PT091 were tested in combination with RIF using SMEDDS in our rapid murine Mtb infection model of dissemination described previously 18, 19 In this rapid model to assess drug efficacy, bacteria a delivered to the lungs and treatment is initiated day 5 post infection before the bacteria disseminate to the spleen. Since we have found that dissemination is important to the pathogenesis of tuberculosis as well as other respiratory pathogens, drugs and drug candidates that control dissemination from the infection sight of the lungs to secondary locations such as the spleen are more efficacious at controlling prolonged infection and relapse 33-37 .…”
Section: Resultsmentioning
confidence: 99%
“…18, 19 In this rapid model animals are infected using the low dose aerosol infection followed by treatment for 10 consecutive days starting 5 days post infection. Compounds were solubilized in specified formulations and delivered at the given route and dose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of these compounds have been found to inhibit the growth of M. tuberculosis H37Rv with an MIC value ≤5 μg/ml, with nine compounds having MIC values between 0.5 and 6.1 μg/ml. Recently, a series of 2-cyclohexyl-5-acylamino-6-N,N-dimethylaminobenzimidazoles derivatives has been synthesized and two, SB-P17G-A20 10d and SB-P17G-C2 10c (Figure 4), have been found to be most effective against clinically pathogenic strains of M. tuberculosis, with MIC values 0.16 and 0.06 μg/ml, respectively [89]. SB-P17G-C2 10c has been found to be highly labile in the presence of mouse and human liver microsomes in comparison to SB-P17G-A20 10d, indicating that it has more acceptable physicochemical properties.…”
Section: Benzimidazolesmentioning
confidence: 99%